ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Home Industri Kaca Grafir di Desa Grujugan Kidul Kecamatan Grujugan Bondowoso) - Damanhuri Damanhuri; Muhammad Firdaus; Yani Dahliani (RELASI : JURNAL EKONOMI, 2013)
Companies need to understand the things that is closely related to customer satisfaction:  quality of  product,  quality of service,  and  price. Based  on this, the aim of this study were to analyze the effect of product quality, service quality, and price  to customer satisfaction  in the  Home Industrial  Glass  Engraving  in  the Grujugan Kidul Village, Grujugan District Bondowoso Regency. This study  are used primary data  and multiple  regression analysis. The results showed  that  the variable  quality of the  product  and  prices  significantly affect  customer satisfaction.  Most of customer  satisfaction  in the  Home Industrial  Glass Engraving are influenced by the quality of the product and the price.